Disinformation, on the rise: An analysis of the fake news on Spanish politics - López-Martín, Álvaro; Gómez-Calderón, Bernardo; Córdoba-Cabús, Alba (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
Through a content analysis, this paper explores the features of fake news on Spanish politics registered on the Maldita.es, Newtral, EFE Verifica and Verificat verification platforms between January 1 and March 31, 2022. These messages are spread mainly through Twitter and Facebook, using the text as support. The predominance of the ideological purpose, the high presence of stories of absolute invention, the shared role of anonymous and supplanted sources, the use of the informative style and the preponderance of left-wing formations as the object of hoaxes are also demonstrated.